Indirect methods of assessing maximal oxygen uptake in rowers: Practical implications for evaluating physical fitness in a training cycle - Klusiewicz, A.; Borkowski, L.; Sitkowski, D.; Burkhard-Jagodzinska, K.; Szczepanska, B.; Ladyga, M. (Journal of Human Kinetics, 2016)
The aim of the study was to evaluate the usefulness of indirect methods of assessment of VO2max for estimation of physical capacity of trained male and female rowers during a training cycle. A group of 8 female and 14 male rowers performed the maximal intensity test simulating the regatta distance (a 2 km test) and a submaximal incremental exercise test on a rowing ergometer. The suitability of the indirect methods of predicting VO2max during the training cycle was evaluated by performing the tests twice: in females at an interval of five months and in males at an interval of seven months. To indirectly estimate VO2max, regression formulas obtained for the linear relationship between the examined effort indices were utilized based on 1) mean power obtained in the 2 km test, and 2) submaximal exercises after the estimation of PWC170. Although the suitability of the two indirect methods of assessment of VO2max was statisticaly confirmed, their usefulness for estimation of changes in physical fitness of trained rowers during the training cycle was rather low. Such an opinion stems from the fact that the total error of these methods (range between 4.2-7.7% in female and 5.1-7.4% in male rowers) was higher than the real differences in VO2max values determined in direct measurements (between the first and the second examination maximal oxygen uptake rose by 3.0% in female rowers and decreased by 4.3% in male rowers).